Green Intellectual Capital, MFCA Peran Green Intellectual Capital dan Material Flow Cost Accounting Terhadap Kinerja Perusahaan Sebagai Perwujudan Energi Berkelanjutan - Himmah, Elok Faiqoh; Putri, Anike; Cristiani, Ester (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the effect of implementing green relational intellectual, green structural capital, green human capital, material flow cost accounting on company performance using return on assets as an indicator. The population in this study are energy sector companies listed on the Indonesia Stock Exchange 2019-2023, using purposive sampling techniques, so the samples used are energy sector companies that are consistent in publishing financial reports and paying attention to their green intellectual capital. The total samples used in the research were 125 research samples. The method used in the research is multiple linear regression analysis test. Based on the results of the analysis, it shows that there is a significant influence of green intellectual capital on company performance. For the material flow cost accounting variable, it also has a significant influence on company performance. Apart from that, simultaneously green intellectual capital which consists of green relational intellectual, green structural intellectual, green human intellectual, and material flow cost accounting also has a significant influence on company performance. In signaling theory, it is said that investors are very interested in investing in the energy sector with investors' main assessment being the implementation of factors that support environmental sustainability. This is because the energy sector is a company that has quite a high emission impact on the environment, even though it provides quite large profits when investing in this sector.